2020
DOI: 10.1002/celc.202001207
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cation Mixing in LiNiO2 toward the Oxygen Evolution Reaction

Abstract: Nickel‐based oxide catalysts are widely used for the oxygen evolution reaction (OER) in alkaline water electrolysis because of their low cost and high activity. In particular, the LiNiO2 catalyst shows high activity. Therefore, to elucidate the fundamental relationship between the local structure, catalyst activity, and stability of LiNiO2, we investigated the cation mixing effect by mixing sites of lithium and nickel ions in the LiNiO2‐based catalysts. Lower degrees of cation mixing lead to higher intrinsic O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…4f, the lower potential limit decreased stepwise from 1.41 V (used in Figs. 4a) to 1.11 V, close to the values generally used in previous studies [44][45][46][47][48][49] . When the lower potential limit was set to 1.41 V, the OER current is optimal and remains stable over multiple CV cycles.…”
Section: Electrochemical Measurementssupporting
confidence: 88%
See 1 more Smart Citation
“…4f, the lower potential limit decreased stepwise from 1.41 V (used in Figs. 4a) to 1.11 V, close to the values generally used in previous studies [44][45][46][47][48][49] . When the lower potential limit was set to 1.41 V, the OER current is optimal and remains stable over multiple CV cycles.…”
Section: Electrochemical Measurementssupporting
confidence: 88%
“…When undergoing the Ni 2+ /Ni III redox, the surface structure of LiNiO 2 transforms and degrades into NiOOH, which has a poor OER activity in the absence of Fe. In contrast, the pristine and structurally unaltered LiNiO 2 , whose real active species has been covered and neglected in previous LiNiO 2 OER studies 44,45,[47][48][49] , exhibits better intrinsic OER activity.…”
Section: Electrochemical Measurementsmentioning
confidence: 98%
“…[37] For the OER, a significant effect was also reported for low concentrations of bivalent and trivalent cations, such as Ba 2 + , Mg 2 + , Zn 2 + , Al 3 + , Cr 2 + and Ca 2 + , for a variety of electrodes. [40][41][42][43][44][45] Bivalent cations strongly impact the OER reaction and DFT calculations [46] have shown that strong binding of cations with the (OER) reaction intermediates negatively impacts the activity. Similarly, multivalent cations negatively impact the Kolbe reaction.…”
Section: Introductionmentioning
confidence: 99%